Impedance of carrier injection at the metal-organic interface mediated by surface states in electron-only tris(8-hydroxyquinoline) aluminium (Alq(3)) thin layers - Garcia-Belmonte, Germa; Bisquert, Juan; Bueno, Paulo R. [UNESP]; Graeff, Carlos Frederico de Oliveira [UNESP] (Elsevier B.V., 2008)
Capacitance spectra of thin (< 200 nm) Alq(3) electron-only devices have been measured as a function of bias voltage. Capacitance spectra exhibit a flat response at high frequencies (> 10(3) Hz) and no feature related to the carrier transit time is observed. Toward low frequencies the spectra reach a maximum and develop a negative excess capacitance. Capacitance response along with current-voltage (J-V) characteristics are interpreted in terms of the injection of electrons mediated by surface states at the metal organic interface. A detailed model for the impedance of the injection process is provided that highlights the role of the filling/releasing kinetics of energetically distributed interface states. This approach connects the whole capacitance spectra to the occupancy of interface states, with no additional information about bulk trap levels. Simulations based on the model allow to derive the density of interface states effectively intervening in the carrier injection (similar to 1.5 x 10(12) cm (2)). (C) 2008 Elsevier B.V. All rights reserved.